Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.1126/science.272.5262.735
|View full text |Cite
|
Sign up to set email alerts
|

The Cytolytic P 2Z Receptor for Extracellular ATP Identified as a P 2X Receptor (P2X 7 )

Abstract: The P2Z receptor is responsible for adenosine triphosphate (ATP)-dependent lysis of macrophages through the formation of membrane pores permeable to large molecules. Other ATP-gated channels, the P2X receptors, are permeable only to small cations. Here, an ATP receptor, the P2X7 receptor, was cloned from rat brain and exhibited both these properties. This protein is homologous to other P2X receptors but has a unique carboxyl-terminal domain that was required for the lytic actions of ATP. Thus, the P2X7 (or P2Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

73
1,602
6
7

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,640 publications
(1,688 citation statements)
references
References 22 publications
(4 reference statements)
73
1,602
6
7
Order By: Relevance
“…P2X 7 R is an intriguing receptor from which pharmacological activation is generally associated to cytotoxic effects (Surprenant et al, 1996;Di Virgilio et al, 1998) therefore leading to the hypothesis that their overexpression or stimulation could be deleterious for cells. Surprisingly, it was found that P2X 7 R is expressed at very high levels in several tumours, compared with Deli et al, 2007;Solini et al, 2008) and was even proposed to represent an early cancer marker (Slater et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…P2X 7 R is an intriguing receptor from which pharmacological activation is generally associated to cytotoxic effects (Surprenant et al, 1996;Di Virgilio et al, 1998) therefore leading to the hypothesis that their overexpression or stimulation could be deleterious for cells. Surprisingly, it was found that P2X 7 R is expressed at very high levels in several tumours, compared with Deli et al, 2007;Solini et al, 2008) and was even proposed to represent an early cancer marker (Slater et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…functioning as a neuromodulator at glutamatergic synapses (Gu and MacDermott, 1997), while millimolar concentrations, released into the extracellular milieu in response to injury, can act, via P2X7, as a DAMP, initiating neuroinflammatory cascades (Fiebich et al, 2014). Secondly, the pore-forming functionality of the P2X7 receptor facilitates the release of larger hydrophilic molecules, up to 900 Da (Surprenant et al, 1996), a process which may be important for initiating neuroinflammation. Indeed, the formation of the P2X7 receptor pore seems to be necessary for the role of the molecule in activating the inflammasome (Monif et al, 2009).…”
Section: The Role Of P2x Receptors In Neuroinflammationmentioning
confidence: 99%
“…The receptor exists in several splice isoforms (A–J) and single nucleotide polymorphisms (SNPs) correlate with several diseases 11, 12. The P2X7R is a ligand‐gated ion channel permeable to Ca 2+ , K + and Na + 13. Following sustained activation or overstimulation, this receptor forms or facilitates formation of pores permeable to large molecules that can lead to cell lysis and death 14, 15.…”
Section: Introductionmentioning
confidence: 99%